Estado estructural y silvicultural de la especie endémica Ocotea strigosa, van der werff (Arrayán), circundante a la Laguna Miraflor, Miraflor, Estelí 2002 - Serrano Sáenz, J.; Toledo Gutiérrez, C.P.; Tapia Lorio, E. del C. Asesor; Alonzo Serrano, E.A. Asesor (Managua (Nicaragua), 2003)
Sumarios (Es, En)
Ilus.
Tesis (Ing Agr)
Keywords: SILVICULTURA; ORGANISMOS INDIGENOS; OCOTEA; VEGETACION; BOSQUE TROPICAL HUMEDO; RESERVAS NATURALES; NICARAGUA; MIRAFLOR; AREAS PROTEGIDAS; ESTELI